A NEW SPECIES OF BOTHRIOCEPHALUS (CESTODA: BOTHRIOCEPHALIDAE) FROM LEPOMIS SPP. (ACTINOPTERYGII: CENTRARCHIDAE) IN NORTH AMERICA - Choudhury, Anindo; Scholz, Tomáš; Beuchel, Joseph S (The Journal of parasitology, 2022)
Based on morphological and molecular data, a new species of tapeworm, Bothriocephalus kupermani n. sp., is described from pumpkinseed, Lepomis gibbosus (Linnaeus, 1758) (type host), and green sunfish, L. cyanellus Rafinesque, 1819 (Actinopterygii: Centrarchidae) in the United States. The new species differs from its North American congeners mainly in the shape of its scolex, which is almost rectangular in dorsoventral and lateral views (nearly parallel margins in the bothrial region), with shallow, wide bothria, and by an extensive field of vitelline follicles that are also variably present, albeit more sparsely, medially in the cortex of the ovarian and uterine areas. This tapeworm appears to be typically associated with Lepomis sunfishes. Examination of museum specimens of Bothriocephalus species from Lepomis spp. indicates that the tapeworm also parasitizes bluegill, Lepomis macrochirus, longear sunfish, Lepomis megalotis, and that previous records of Bothriocephalus cuspidatus and Bothriocephalus claviceps in these fishes are of the new species, B. kupermani.
Keywords: Tapeworms; Cestoda; Animals; United States; Fishes; Perciformes; cestodózy; zvířata; Taxonomy; ryby; Cestode Infections; Bothriocephalidea; Canada; North America; Lepomis; Morphology; Bothriocephalus; Severní Amerika